A knowledge management model for firms in the financial services industry. (25th September 2013) - Held, Carsten; Duncan, Glen; Yanamandram, Venkat
The financial services industry faces many demanding challenges. Firms within this industry are predominantly knowledge–based, as are most of the industry's products, processes and services. The application of knowledge management represents a clear opportunity for financial services firms to confront challenges. However, no industry specific knowledge management model for financial services exists. The contribution of this paper is to develop such a model. A multi–level model is constructed by building upon and integrating the Resource–Based/Knowledge–Based Views (RBV/KBV) of the firm, knowledge strategy, methods, knowledge domains, and communities. Based on case study research, a set of guidelines is then proposed to aid in the implementation of the model. The model and guidelines offer new opportunities to become more efficient and effective in financial firms.